A Foresight on Perceived Supervisor Support, Job Conditions, Gender Differences and Perceived Organizational Support - Aboul-Ela, Ghadeer Mohamed Badr ElDin (Archives of Business Research, 2018)
The purpose of this research is to analyse the effect of perceived supervisor support, job conditions and gender differences on perceived organization support. Previous literature was explored, and accordingly research hypotheses were posed. Employees working in the call centres of the multinational mobile communication organizations were selected as the sample of the study. Interviews with Key personnel along with experts Human Resources professors were held prior to distributing the questionnaires with the objective of exploring the selected domain characteristics. Research questionnaire was developed using previously published, sound and reliable scales to measure the selected constructs. A total number of 700 self-administered questionnaires were distributed in Cairo and Giza governorates. Statistical analysis was conducted and the results showed a positive relationship between perceived supervisor support and perceived organization support, job conditions and perceived organization support and that females possessed higher levels of felt organization support compared to males. The discussion of results, managerial implications, and research limitations were explored based on the research findings.